Markpackning och regenerering av markstruktur - Alexandersson, Susanne (SLU/Dept. of Soil and Environment, 2017)
This study examines soil compaction and its effect on soil properties, how to avoid compaction and how to regenerate damaged soil structures. One central focus that the study deals with is what importance earthworms have in soil compaction processes. The focus on earthworms is interesting because they are important for the soil structure and therefore they play an important role in soil compaction processes. Furthermore, the importance of earthworms in soil compaction processes is yet an understudied area in agricultural research and related applied studies. This study is based on existing academic literature and applied studies on soil structure and soil compaction. In addition to this, the study also presents novel information of practical experiences which have been collected through interviews with professionals in Sweden.